Description of the female of Ctenodontina mochica Lamas, revalidation of Ctenodontina carrerai (Hull) stat. rev., and comments on the taxonomy and distribution of Peruvian species of Ctenodontina Enderlein (Diptera: Asilidae: Asilinae) - Sánchez, Pável; Camargo, Alexssandro (Zootaxa, 2021)
This work analyzes the status of Peruvian species of Ctenodontina Enderlein, provides the description of the hitherto unknown female of Ctenodontina mochica Lamas, and proposes the revalidation of Ctenodontina carrerai (Hull) stat. rev. (currently regarded as a junior synonym of Ctenodontina maya Carrera & d’Andretta). Additionally, some comments about taxonomy, diagnostic features of male terminalia and distribution of four Peruvian Ctenodontina species, including a modification to the existing key to known species and a map updating their distribution records are given. We report Pachitea Melichar (Hemiptera: Cicadellidae) as prey of Ctenodontina nairae Vieira.